Peran Transformasi Pendidikan Ilmu Sosial Memperkuat Kemampuan Berpikir Kritis Mahasiswa Era Digital - Musadalisam (Yayasan Cerdas Pedia Indonesia, 2025)
This narrative literature review systematically examines the transformative role of social science education in strengthening critical thinking and social attitudes among university students in the digital era. Utilizing critical interpretive synthesis methodology, the study analyzes 80-100 peer-reviewed articles from Scopus (2020-2025) to identify key implementation mechanisms and pedagogical effectiveness indicators. The research reveals that constructivist learning environments, collaborative problem-solving, transformative pedagogy, and strategic technology integration constitute essential components for meaningful educational transformation. Empirical evidence demonstrates that integrated pedagogical strategies including problem-based learning (effect size 0.82), flipped classroom approaches, and hybrid learning models simultaneously develop critical thinking abilities and prosocial attitudes through peer interaction, reflective practice, and authentic community engagement experiences. The integrated theoretical model reveals significant synergistic effects between cognitive and socio-affective development dimensions. For Indonesian higher education contexts, successful implementation requires strategic alignment with Kurikulum Merdeka policy frameworks, institutional systemic change, comprehensive faculty professional development, and continuous evaluation mechanisms.